Airborne dust distribution in a farrowing pen in dependence of other microclimatic parameters during spring-summer period - Boris Antunović (Italian Journal of Animal Science, 2010)
The study was carried out in a farrowing pen during 6 production cycles of 24 days in the spring-summer period. The effect of season and other microclimate parameters on airborne dust concentration was investigated. Study results showed a decrease in airborne dust concentration in summer period that yielded negative correlation with air temperature (P<0.05). Relative humidity was expected to decrease due to higher ventilation rates, however, a significant increase was recorded in summer (P<0.05) because of higher evaporation caused by floor wash. The decrease in airborne dust concentration was ascribed to temperature elevation due to intensified ventilation rate and relative humidity resulting in higher rate of dust settling.